Association of Existence of Third Places and Role Model on Suicide Risk Among Adolescent in Japan: Results From A-CHILD Study - Fujiwara, Takeo; Doi, Satomi; Isumi, Aya; Ochi, Manami (Frontiers in Psychiatry, 2020)
Objective: Low self-esteem among adolescents can be considered a risk factor for suicidal behavior in adolescents. Thus, the purpose of this study is to investigate the association between the existence of a third place and role model on self-esteem among adolescents in Japan, where low self-esteem is prevalent among adolescents. Methods: We analyzed data from the 2016 Adachi Child Health Impact of Living Difficulty (A-CHILD) study, in which a school-based questionnaire was conducted among children in grades 4, 6, and 8 living in Adachi City, Tokyo (N=1609). Children self-rated their own levels of self-esteem. Low self-esteem was defined as lower 10 percentile group. The existence of a third place was defined as a place where children spent time after school other than the home or school campus, and role model was defined as having someone, other than a parent, who they looked up to, and these concepts were assessed via questionnaire. Results: Adolescents without a third place and role model accounted for 10.5% and 6.1%, respectively. We found that children who lacked a third place also showed a significant association with low self-esteem (OR: 1.75, 95% confidence interval (CI): 1.09-2.81), and those who lacked a role model were 3.34 times more likely to have lower self-esteem (95% CI: 1.98-5.62). Conclusion: The existence of a third place and a role model may be important to prevent low self-esteem among adolescents in Japan.